Supporting patients with heart failure with digital therapeutics—A pilot study in Germany. (December 2022) - Reif, S.; Schubert, S.; Stiefel, J.; Husri, F.; Fischlein, T.; Pauschinger, M.; Klucken, J.
Objective: Continuous monitoring and targeted behavioral interventions have been shown to improve health status and quality of life for heart failure patients. Digital therapeutics offer the possibility to make more frequent monitoring and targeted behavioral interventions available for more people. Methods: We conduct a pilot study with 71 patients who were given a smartphone app and wearables for a 3-month period. Clinical indicators as well as patient-reported outcomes were collected at entry and exit examinations. Results: The New York Heart Association class remained stable or improved. Most quantitative outcome measures improved (6-minute walk test distance + 21 m, Kansas City Cardiomyopathy Questionnaire summary score + 6.0 points, European Heard Failure Self-care Behavior Scale summary score + 6.6 points, correct answers in the Atlanta Heart Failure Knowledge Test + 2.1), although the changes were mainly not significantly different from zero. There was no change in EQ-5D weight and 9-item Shared Decision-Making Questionnaire summary score. Conclusions: This before–after comparison shows that an app-based intervention can work as a digital therapeutic for heart failure patients.